A Multi-Topic Bystander Intervention Program for Upper-Level Undergraduate Students: Outcomes in Sexual Violence, Racism, and High-Risk Alcohol Situations - Hennessy Garza, Rose (Journal of interpersonal violence, 2023)
Few bystander intervention trainings programs have evaluated behavioral outcomes in previously trained upper-level undergraduate students. Rigorous study designs are necessary to understand how multi-topic programs influence student outcomes to intervene against sexual violence, racism, and high-risk alcohol situations. A single-session bystander training for emphasizing communication strategies was developed for juniors and seniors on a private, Midwestern college campus. The training addressed sexual violence, racism, and high-risk alcohol situations and was evaluated using a randomized waitlist-control design in student-housing units. Online Qualtrics surveys were completed by 101 student participants (57 in the intervention group and 44 in the control group). Students responded to nine harm scenarios involving sexual violence, racism, and high-risk alcohol situations at baseline and 7 weeks follow-up. Between-group changes in scores were compared to determine the effect of the program on students’ (a) readiness to intervene; (b) confidence to intervene; (c) bystander behaviors among students who witnessed actual or potentially harmful events; and (d) bystander reports of their experiences. Qualitative analysis assessed how the program influenced the use of positive verbal communication strategies. Program effects increased positive bystander experiences when helping someone who had too much to drink and needed assistance. Over time both groups reported increased confidence levels to intervene when someone intoxicated was being isolated with sexual intent. There were no further significant findings in readiness, confidence, behaviors, or other experiences, though some positive nonsignificant trends emerged. The program demonstrated little efficacy. Results suggest opportunities to improve bystander outcomes in low-risk primary prevention situations and racist scenarios, suggesting that targeted intervention of these outcomes may be useful when developing programming with previously-trained students. As universities expand prevention work beyond the first year, lessons learned may help inform multi-year programming across health topics to prevent harm and create healthier college campuses.